Dakwah Via Social Media: Opportunities and Challenges In Indonesia - Suntoro, Adib Fattah (KOLABORASI: Journal of Multidisciplinary, 2024)
This article explores the increasing use of social media as a new kind of dakwah. Opportunities and obstacles that social media dakwah advocates will face, particularly in the Indonesian setting, are the primary emphasis of this article. This study aims to determine the efficacy of social media as a voice and to explain the potential and obstacles in Indonesia. This study employs descriptive qualitative methodology by collecting data via a literature review. This study's findings were gathered from a variety of dakwah science-related sources, including scientific journal publications, reference books, and online reports from research institutes. The findings demonstrate that social media is an effective and efficient method for propagating Islam. Therefore, social media provides several options for dakwah, including accessibility, reach, and affordability. On the other hand, social media presents substantial obstacles for dakwah activists, such as the necessity for dakwah activists to restrict the propagation of bad information and online hoaxes